Global bank capital and liquidity after 30 years of Basel accords - Harald A. Benink (Journal of Risk and Financial Management, 2020)
In this paper we analyze the effectiveness of more than 30 years of efforts by international banking supervisors, working together in the Basel Committee on Banking Supervision, to harmonize capital and liquidity standards for internationally active banks. Notwithstanding the great efforts and progress made by international banking supervisors since the financial crisis of 2007–2009, two important issues require further attention. First, although bank capital ratios have been raised significantly since the recent financial crisis, they are still at historically low levels. In a world in which global debt ratios have risen even further during the past decade, this is a worrying signal of fragility in the global financial system. Second, bank liquidity requirements may have become too complex and could also have unintented and unpredictable interaction effects with bank capital requirements.
Keywords: 330; bank capital; bank liquidity; basel committee; great financial crisis